2008
DOI: 10.3354/meps07532
|View full text |Cite
|
Sign up to set email alerts
|

Spillover from six western Mediterranean marine protected areas: evidence from artisanal fisheries

Abstract: Species that have shown strong responses to protection are those that have moderate vagility in relation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
181
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(191 citation statements)
references
References 50 publications
8
181
0
2
Order By: Relevance
“…Our estimates of spillover distance are consistent with studies of large-scale partial-protection marine protected areas that find even greater spillover distances (Murawski et al 2005), with studies of adult movement patterns showing similar or greater distances of movement across reserve boundaries (for example (Samoilys 1997;Kelly & MacDiarmid 2003;Topping et al 2005), and with estimates from spillover studies that did not meet our inclusion criteria (Abesamis & Russ 2005;Goni et al 2008;Harmelin-Vivien et al 2008;Williams et al 2009). However, in all of these cases, spillover acts at relatively small scales such that single reserves cannot sustain entire fished stocks (through spillover alone; they may be able to provide this service through larval export).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our estimates of spillover distance are consistent with studies of large-scale partial-protection marine protected areas that find even greater spillover distances (Murawski et al 2005), with studies of adult movement patterns showing similar or greater distances of movement across reserve boundaries (for example (Samoilys 1997;Kelly & MacDiarmid 2003;Topping et al 2005), and with estimates from spillover studies that did not meet our inclusion criteria (Abesamis & Russ 2005;Goni et al 2008;Harmelin-Vivien et al 2008;Williams et al 2009). However, in all of these cases, spillover acts at relatively small scales such that single reserves cannot sustain entire fished stocks (through spillover alone; they may be able to provide this service through larval export).…”
Section: Discussionsupporting
confidence: 74%
“…Growing evidence from theoretical models and empirical studies suggests that higher abundances inside reserves can lead to spillover of adults to nearby fished areas (Rowley 1994;Roberts et al 2001;Goni et al 2008;Kellner et al 2008;Perez-Ruzafa et al 2008). Spillover is typically observed as declining patterns of abundance or catch across reserve boundaries, although there may be no detectable pattern of decline in abundance if fishing effort is intense surrounding the reserve.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the species that responded to protection with higher catches near the border, such as Dentex dentex, Mullus surmuletus, Phycis phycis, Sciaena umbra and Scorpaena porcus, are important target species of artisanal fisheries (García-Rodríguez et al 2006, Forcada 2007, Goñi et al 2008. Moreover, these species represent the highest proportion of the catch and the greatest income for artisanal fisheries (García-Rodríguez et al 2006, Forcada 2007, Goñi et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these species represent the highest proportion of the catch and the greatest income for artisanal fisheries (García-Rodríguez et al 2006, Forcada 2007, Goñi et al 2008. Uranoscopus scaber fished on sandy bottoms at different distances (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, extensive study has demonstrated that fully protected no-take marine reserves can be important tools for protecting ecosystems from extractive activities and restoring marine habitats and species. Ecologic field studies of marine reserves have demonstrated positive effects on biologic measures (e.g., biomass and density) inside their borders (5)(6)(7) and in the adjacent fished waters (8,9). Consequently, governments and local communities are increasingly considering marine reserves or networks of reserves as a means of reducing threats to marine ecosystems.…”
mentioning
confidence: 99%